Nanonization and Deformable Behavior of Fattigated Peptide Drug in Mucoadhesive Buccal Films - Kim, Woojun; Ngo, Hai V.; Nguyen, Hy D.; Park, Ji Min; Lee, Kye Wan; Park, Chulhun; Park, Jun Bom; Lee, Beom Jin (Pharmaceutics, 2024)
This study was tasked with the design of mucoadhesive buccal films (MBFs) containing a peptide drug, leuprolide (LEU), or its diverse nanoparticles (NPs), for enhanced membrane permeability via self-assembled nanonization and deformable behavior. An LEU-oleic acid conjugate (LOC) and its self-assembled NPs (LON) were developed. Additionally, a deformable variant of LON (d-LON) was originally developed by incorporating l-α-phosphatidylcholine into LON as an edge activator. The physicochemical properties of LON and d-LON, encompassing particle size, zeta potential, and deformability index (DI), were evaluated. MBFs containing LEU, LOC, and NPs (LON, d-LON) were prepared using the solvent casting method by varying the ratio of Eudragit RLPO and hydroxypropyl methylcellulose, with propylene glycol used as a plasticizer. The optimization of MBF formulations was based on their physicochemical properties, including in vitro residence time, dissolution, and permeability. The dissolution results demonstrated that the conjugation of oleic acid to LEU exhibited a more sustained LEU release pattern by cleaving the ester bond of the conjugate, as compared to the native LEU, with reduced variability. Moreover, the LOC and its self-assembled NPs (LON, d-LON), equivalent to 1 mg LEU doses in MBF, exhibited an amorphous state and demonstrated better permeability through the nanonization process than LEU alone, regardless of membrane types. The incorporation of lauroyl-L-carnitine into the films as a permeation enhancer synergistically augmented drug permeability. Most importantly, the d-LON-loaded buccal films showed the highest permeability, due to the deformability of NPs. Overall, MBF-containing peptide NPs and permeation enhancers have the potential to replace parenteral LEU administration by improving LEU druggability and patient compliance.
Keywords: deformability index; enhanced permeability; formulation design; in vitro evaluation; leuprolide-oleic acid conjugate; mucoadhesive buccal film; self-assembled nanonization